Creation of multicomponent mix based on lactic bacteria consortium for flour enrichment - Alimkulov, Zheksenkul; Zhiyenbayeva, Saule; Baygazieva, Gulgaisha; Rustemova, Ainash; Batyrbayeva, Nurgul; Bayisbayeva, Meruert (International Journal of Engineering and Technology, 2018)
This article presents the results on creating the probiotic preparation with inclusion of microorganisms of highly productive lactic bacteria cultures with high biosynthetic and bactericidal properties. Conditions for production of bacterial preparation and multicomponent mix for flour enrichment and bread making were developed. Composition of the produced improving agent and premix for flour enrichment was studied and conditions for flour enrichment using the produced biological improving agent based on lactic bacteria were developed. Technological parameters of flour semi-products where determined on addition of the enriched flour. It was determined that produced improving agent plays a key role in transformation of protein-proteinase and carbohydrate-amylase flour complex, thereby improving the structural-mechanical properties of dough and further resulting in production of elastic crumb with thin-walled and even texture.
Keywords: Flour Enrichment; Micronutrients; Probiotic Preparation; Multicomponent Mixes; Improver; Lactic Acid Bacteria Isolates.